FACE-ing new knowledge - The Star, (2012)
SERDANG: Datin Seri Rosmah Mansor hopes a new research centre based in Universiti Putra Malaysia (UPM) will boost scientific research on the development of children, teenagers and family institution as well as help generate new knowledge.